REGIONAL RISK ASSESSMENT OF HIGHLY PATHOGENIC AVIAN INFLUENZA IN THE BORDER OF INDONESIA AND MALAYSIA: A SOCIO ECONOMIC PERSPECTIVE - Ilham, Nyak; Iqbal, Muhammad (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
The result  of  the  study  shows  that  the  extent  of  both  active  and  passive surveillance was still low due to large coverage area and lack of report cases of  Highly Pathogenic Avian Influenza (HPAI)  from poultry farmers. The level of coordination among cross-border institutions was still relatively worst so that the illegal trade was still occurred in the checkpoints and other entry points along the cross-border line. The movement of poultry and poultry products was still risky  since the  traders tend to be actively visiting and catching the poultry in the sheds. There were some handicaps  in line  with  local  socio  culture  such  as  multi  events  festivity  with  high  consume  of chickens and cock fighting activity in some spotted areas.  It  is suggested that active surveillance system together with zoonotic  campaign should be implemented in order to obtain the immediate data  and information as well as  to attract poultry farmers to provide reporting on the case of HPAI in the respected areas.